Adaptación de lentes de contacto en paciente masculino de 37 años con miopía magna. - Estrada Estrada, Erika Viviana (2023)
This case study deals with a clinical case of high myopia and is the product of concern about the great increase in the prevalence of myopia. We analyze the etiopathogenesis and the various methods of control of myopia, with special attention to the adaptation of contact lenses. The clinical analysis of this patient focuses on improving the quality of life of a 37-year-old male patient who progressively lost visual field over the years since he was 20 years old, he presented blurred vision from afar, so he went to an optometric consultation. and begins to correct myopia identified with contact lenses, his measurements have been changing. The objective of the study is to optimize the vision of a 37-year-old male patient with high myopia with the use of contact lenses. It is concluded that high myopia is a progressive disease, as evidenced in this patient. A disease that, although it cannot be paralyzed, can stop its progression with the proper use of lenses, with patient care, with scheduled visits to the optometrist.